Terapi rasional-emotif perilaku untuk menurunkan tingkat depresi pada wanita - Andita Faradilla (Universitas Muhammadiyah Malang, 2021)
The subject is a college student woman who has changes in functionality in everyday life. Subject has a bad view of herself and tend to like to compare herself with others, especially physical problems. As a result, subject tend to be easily sad, lose interest, often feel tired and sometimes bring up suicidal thoughts. The assessment methods used were clinical interview, observation, and psychological tests, namely the Weschler Adult Intelligence Scale, graphics, Thematic Apperception Test, the Beck Depression Inventory II scale and WHODAS. Subject was diagnosed with major depressive disorder with moderate level of functioning. The intervention used was rational-emotive behavior therapy which was composed of five sessions. This therapy is used with the aim of reducing depression levels through changing irrational beliefs to become more rational. The results of the intervention showed a decrease in the subject's level of depression as indicated by changes in the scores obtained before and after the intervention was given.